Influence of sulfur partial pressure on the structural performance of Cu2ZnSnS4 solar cells. (1st March 2021) - Li, Xiaoming; Hao, Ruiting; Gu, Kang; Guo, Jie; Mo, Jinghui; Fang, Shuiliu; Liu, Xinxing; Li, Yong; Wei, Guoshuai; Liu, Bin; Wang, Lu; Sun, Shuaihui; et al.
Abstract: CZTS precursors was deposit by sputtering, and then annealed in the range of 1000–5000 Pa sulfur partial pressure. The partial pressure of sulfur is controlled by changing the amounts of sublimed sulfur in a small, sealed quartz tube. As the sulfur partial pressure increased, the crystallinity of CZTS thin film was improved; surface voids and secondary phases were reduced; the thickness of MoS2 at low sulfur partial pressure ranging from 1000 Pã3000 Pa. After the sulfur partial pressure reaching 5000 Pa, the thickness of MoS2 increased significantly. The secondary phases, voids and MoS2 reduced the carrier collection in the 500–800 nm wavelength range, resulting in lower short-circuit current density and fill factor. Finally, the device based on the 3000 Pa sulfur partial pressure achieved the highest photoelectric conversion efficiency of 4.25% ( V OC : 0.648 V, I SC : 15.25 mA/cm 2, FF : 43.02%).